The sprint mechanics assessment score: A qualitative screening tool for the in-field assessment of sprint running mechanics - Bramah, C.; Tawiah-Dodoo, J.; Rhodes, S.; Elliott, J. D.; Dos'Santos, T. (The American Journal of Sports Medicine, 2024)
Background Qualitative movement screening tools provide a practical method of assessing mechanical patterns associated with potential injury development. Biomechanics play a role in hamstring strain injury and are recommended as a consideration within injury screening and rehabilitation programs. However, no methods are available for the in-field assessment of sprint running mechanics associated with hamstring strain injuries.